The Relationship of Ludwig Van Beethoven and Johann Nepomuk Mälzel Through the Metronome - Göknil Özkök Sezener (Konservatoryum)
Throughout history, music has been transformed by composers’ works, both musically and technically, with different and new ideas. Some composers marked the end of an era, while others marked the beginning of a new era and art movement. Some composers brought a new perspective and innovations to music in their own time and inspired the ages that came after them. But no composer has elevated the sonata, concerto, chamber music and symphony form to a level that is considered almost unattainable like Ludwig van Beethoven. The works of the composer, who took his place as a turning point in the transition from the Classical Period to the Romantic Period, are analyzed as belonging to both periods. For this reason, he revolutionized music in his time as a composer whose bold innovations were accepted, applauded and respected. The political upheavals of his time, popular uprisings and wars, Beethoven’s solution-oriented interest in social issues and problems, all find a place in his correspondence, discourse and most importantly in his music. In this study, in addition to the changes that L.v. Beethoven, an innovative and open personality to the changes in the world, created in his music; his relationship with the metronome, which is an 19th century invention and patented by Johann Nepomuk Mälzel, a German inventor, musician and designer of interesting inventions and projects in the world of show business, his first use in his works and the process of his musical partnerships with this inventor will be included.